A placebo-controlled randomized trial of D-cycloserine augmentation of cue exposure therapy for smoking cessation. Issue 1 (2nd January 2019) - Otto, Michael W.; Pachas, Gladys N.; Cather, Corinne; Hoeppner, Susanne S.; Moshier, Samantha J.; Hearon, Bridget A.; Ward, Heather Burrell; Laffer, Alexandra B.; Smits, Jasper A. J.; Evins, A. Eden
ABSTRACT: Recent studies underscore the importance of studying d-cycloserine (DCS) augmentation under conditions of adequate cue exposure treatment (CET) and protection from reconditioning experiences. In this randomized trial, we evaluated the efficacy of DCS for augmenting CET for smoking cessation under these conditions. Sixty-two smokers attained at least 18 hours abstinence following 4 weeks of smoking cessation treatment and were randomly assigned to receive a single dose of DCS (n=30) or placebo (n=32) prior to each of two sessions of CET. Mechanistic outcomes were self-reported cravings and physiologic reactivity to smoking cues. The primary clinical outcome was 6-week, biochemically-verified, continuous tobacco abstinence. DCS, relative to placebo, augmentation of CET resulted in lower self-reported craving to smoking pictorial and in vivo cues (d = 0.8 to 1.21) in a relevant subsample of participants who were reactive to cues and free from smoking-related reconditioning experiences. Select craving outcomes were correlated with smoking abstinence, and DCS augmentation was associated with a trend toward a higher continuous abstinence rate (33% vs. 13% for placebo augmentation). DCS augmentation of CET can significantly reduce cue-induced craving, supporting the therapeutic potential of DCS augmentation when applied under appropriate conditions for adequate extinction learning.